Reproductive biology and feeding habits of Stenocercus caducus (Iguanidae) in semideciduous forest in central Brazil. - Waldemar Avila, Robson; Ferreira, Vand Lucia; Maidana, Clelia (My University, 2008)
Sexual dimorphism, reproduction and diet are described for Stenocercus caducus from semideciduous forest, in Mato Grosso do Sul state, Central Brazil. Lizards are collected in pitfall traps from December 2000, to December 2001. Sexual dimorphism in S. caducus is apparent, mainly in coloration; although females reach a larger SVL than males. A wide variety of arthropods are fed by S. caducus, with ants and termites numerically, and orthopterans and beetles volumetrically the most common prey items. Ontogenetic differences in diet were noted for S. caducus, with juveniles feeding on lesser prey types and smaller sized prey than adults. The reproduction was seasonal, concentrated in the rainy season, with deposition of more than one clutch per season.